REALITAS PELAKSANAAN HUKUM ISLAM PERSPEKTIF FATWA MAJELIS ULAMA INDONESIA DAN PERUNDANG-UNDANGAN DI INDONESIA - Nilhakim, Marilang, Kurniati (FAKULTAS HUKUM UM PAREPARE, 2021)
The majority of Indonesia's population is Muslim, with a long history of Islamic growth. This historical (historical) aspect is a fact of the roots of Islam in accompanying the growth journey of Indonesian citizens which is not only related to religion, social life, especially the life of the nation and state. The emergence and establishment of such Muhammadiyah and Nahdlatul Ulama as mass organizations with a religious character have shared the pattern of growth and journey of Islamic law in Indonesia with the birth of fatwas and their decisions. Positive progress in the national legal system in Indonesia was seen during the New Order era, the growth of fatwas in Indonesia faced positive progress, namely the occurrence of the Indonesian Ulema Council (MUI). The procedure in this research is a qualitative procedure with a survey of documents in the form of an MUI fatwa. In collecting information, the researcher reviews the library research, after that it is collected so that a normative (syar'i) and juridical theological approach is carried out. With the establishment of the MUI, recorded in history up to now, there have been many MUI fatwas and advices referred to as products of Islamic legal thought which have become a reference source in various laws and regulations. In the Indonesian constitution, the MUI lies in the role of elements of the administrative infrastructure. Because MUI is an organization of Muslim Ulama who has the duty and role to empower citizens or Muslims, so that MUI is an organization that exists within the community, not part of state-owned institutions or representing a country. The reality of the application of Islamic law from the perspective of the MUI fatwa and legislation in Indonesia from an abstract regulatory perspective, a fatwa will be binding if it has been in the form of a certain law by an authorized institution, for example a law or regional regulation (PERDA) so that it becomes a positive law. There are also times when there are people or Muslim citizens who want to carry out a fatwa so that it can be an individual religious understanding, but not as a legal obligation.